Severity of Liver Disease Affects HCV Kinetics in Patients Treated with Intravenous Silibinin Monotherapy. Issue 2 (February 2015) - Canini, Laetitia; DebRoy, Swati; Mariño, Zoe; Conway, Jessica M; Crespo, Gonzalo; Navasa, Miquel; D'Amato, Massimo; Ferenci, Peter; Cotler, Scott J; Forns, Xavier; Perelson, Alan S; Dahari, Harel
Background: HCV kinetic analysis and modelling during antiviral therapy have not been performed in decompensated cirrhotic patients awaiting liver transplantation. Here, viral and host parameters were compared in three groups of patients treated with daily intravenous silibinin (SIL) monotherapy for 7 days according to the severity of their liver disease. Methods: Data were obtained from 25 patients, 12 non-cirrhotic, 8 with compensated cirrhosis and 5 with decompensated cirrhosis. The standard-biphasic model with time-varying SIL effectiveness (from 0 to final effectiveness [εmax ]) was fitted to viral kinetic data. Results: Baseline viral load and age were significantly associated with the severity of liver disease ( P <0.0001). A biphasic viral decline was observed in most patients with a higher first phase decline in patients with less severe liver disease. The εmax was significantly ( P ≤0.032) associated with increasing severity of liver disease (non-cirrhotic εmax [se ]=0.86 [0.05], compensated cirrhotic εmax =0.69 [0.06] and decompensated cirrhotic εmax =0.59 [0.1]). The second phase decline slope was not significantly different among groups (mean 1.88 ±0.15 log10 IU/ml/week, P =0.75) as was the rate of change of SIL effectiveness (k=2.12/day [se =0.18/day]). HCV-infected cell loss rate (δ [se ]=0.62/ day [0.05/day]) was high and similar among groups. Conclusions: The high loss rate of HCV-infected cells suggests that sufficient dose and duration of SIL might achieve viral suppression in advanced liver disease.